Audiovisual translation in primary education. Students’ perceptions of the didactic possibilities of subtitling and dubbing in foreign language learning - Fernández-Costales, Alberto (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2021)
This paper investigates the use of Audiovisual Translation (AVT) as a didactic tool in primary education. Several studies confirm that subtitling and dubbing are beneficial for productive and receptive skills, vocabulary acquisition, translation competence, and learners’ motivation and engagement. However, research in the field has been devoted primarily to university students enrolled in translation and language programmes, and there is a dearth of papers exploring the use of AVT in early educational stages. This paper is intended to fill this gap by examining the perceptions of primary education students on the use of interlingual subtitling and creative dubbing in learning English at school. The sample includes 120 students from 10 public primary schools in Spain who participated in a 3-month teaching study. The research tool was a student questionnaire aimed at gathering their perceptions on the use of AVT; this survey was complemented with in-class observations. Results underline the favourable views students had on the use of AVT in language learning in primary education, with a slight preference for dubbing over subtitling. This outcome brings to the fore the educational possibilities of AVT, which may be a useful resource in language teaching.